ANALISIS DAMPAK KARAKTERISTIK KEPRIBADIAN DAN GAYA KEPEMIMPINAN OTOKRATIS TERHADAP KINERJA KARYAWAN PADA ATTEENAHIJAB JOMBANG - Firmana, Anggie Ayundea (Department of Management, 2018)
The purpose of this study is, to describe the characteristics of personality, autocratic leadership, and the performance of the employee. The next is, to know whether the significantly characteristics of the personality can influence performance of the employee. The third, to know the significantly of the leadership to influence on employee performance. Futhormore, to determine wheter the characteristics of the personality and autocratic leadership on the employee performance. Fifth, to know among the characteristics of personality and the autocratic of leadership form that contribute of the largest influence on performance of the employee. The population of all employees, total sample 41 and the sampling technique of total sampling. The writer used the technique of collecting data is questionnaires and documentation. In this reaserch the analytical tool using a range of scales and multiple linier analysis. The result of the analysis part of the scale characteristics of the personality included the criteria is quite good, the autocratic leadership included the criteria is fairly strong and employee performance include the criteria is quite good. The result of hypothesis testing is stating the characteristic of personality and the significant the autocratic of the leadership can influence on the employee performance. Personality characteristics are variable that have the greatest contribution to employee performance.